Effect of the COVID-19 Pandemic and Isolation Measures on the Mental Health Well-Being of Sixth Form Grammar School Students in Cumbria - Medhini Varma; Pulkit Kaushal (BJPsych Open, 2025)
Aims: COVID-19 affected many countries globally, including the UK, to which the UK responded by placing lockdown measures throughout the country. This meant that many people were restricted in their everyday lives, including students. This study is used to understand the impact of these measures on sixth form students.